Preferential production of RNA rings by T4 RNA ligase 2 without any splint through rational design of precursor strand - Chen, Hui (Nucleic Acids Res, 2020)
Rings of single-stranded RNA are promising for many practical applications, but the methods to prepare them in preparative scale have never been established. Previously, RNA circularization was achieved by T4 RNA ligase 2 (Rnl2, a dsRNA ligase) using splints, but the yield was low due to concurrent intermolecular polymerization. Here, various functional RNAs (siRNA, miRNA, ribozyme, etc.) are dominantly converted by Rnl2 to the rings without significant limitations in sizes and sequences. The key is to design a precursor RNA, which is highly activated for the efficient circularization without any splint. First, secondary structure of target RNA ring is simulated by Mfold, and then hypothetically cut at one site so that a few intramolecular base pairs are formed at the terminal. Simply by treating this RNA with Rnl2, the target ring was selectively and efficiently produced. Unexpectedly, circular RNA can be obtained in high yield (>90%), even when only 2 bp form in the 3′-OH side and no full match base pair forms in the 5′-phosphate side. Formation of polymeric by-products was further suppressed by diluting conventional Rnl2 buffer to abnormally low concentrations. Even at high-RNA concentrations (e.g. 50 μM), enormously high selectivity (>95%) was accomplished.